Management Therapy of ST-Segment Elevation Myocardial Infarction: A Literature Review - Novrianti, Irma; Wijaya, Dhani; Mustamin, Faizal; Wijayanti, Sari (Journal of Islamic Pharmacy, 2020)
Coronary Heart Disease (CHD) is the cardiovascular disease due to plaque build-up in the coronary artery, reducing the blood follow to the heart. STEMI (ST-segment elevation myocardial infarction) is the CHD due to the ST-segment elevation in 12 and the cardiac marker elevation as Troponin I. The elevation is due to a blockage in the coronary artery, causing the blood perfusion and oxygen supply for the heart to decrease. The objective of the article review is to describe the correct STEMI therapy based on the research findings and references listed in the literary review. This review was made with the study of literature published in 1993-2019. Conclusion: STEMI therapy management is discomfort management and reperfusion therapy. The reperfusion therapy is aimed to recover the myocardial blood flow, to heal the heart, and to reduce the mortality level. The primary coronary artery reperfusion can be administered with the primary percutaneous coronary intervention (PCI). PCI can open a blockage in the coronary artery and has a good effect on the short-term and long-term clinical results. Besides, it reduces the death risk, myocardial infarction, or repetitive stroke. Meanwhile, reperfusion using fibrinolytics is conducted when PCI is unavailable. Moreover, anticoagulant, antithrombotic, and vasodilators are supporting therapies for STEMI patients to reduce chest pain and prevent reinfarction